Localization effects and pseudogap state in YBa₂Cu₃O₇– single crystals with different oxygen content - Obolenskii, M.A.; Vovk, R.V.; Bondarenko, A.V.; Chebotaev, N.N. (Физика низких температур, 2006)
We have investigated the evolution of the temperature dependence of the in-plane and
off-plane conductivity of YBa₂Cu₃O₇₋δ single crystals due to the decrease of the oxygen content in
the samples caused by a heat treatment. The concentration dependence of the in-plane and
off-plane energy gaps has been determined. It has been shown that the enhancement of the localization
effects results in a suppression of the pseudogap state. At the same time, the decrease of the
oxygen content results in a relative narrowing of the temperature interval in which the regime of
the fluctuating conductivity is realized.